Analysis of the Effect of Economic and Political Variables on Economic Growth in Indonesia - Milla Zahidalutfa (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
This study aims to determine the effect of economic and political variables on economic growth in Indonesia with a research period of 2011-2016 and as many as 33 provinces. The variables used in this study are Investment, Labor Force Participation Rate (TPAK), School Participation Rate (APS), Indonesian Democracy Index (IDI) and Gross Regional Domestic Product (GRDP). The analytical tool used in this study is the Random Effect Model (FEM). The results of the analysis show that the Investment, APS and IDI variables have a positive and significant effect on economic growth in Indonesia, while the LFPR variable is not statistically significant and cannot explain economic growth in Indonesia.